2012
DOI: 10.1002/ange.201205164
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Ionization of Cobaltocene: The Metallocene Molecule Revealing Zero Kinetic Energy States

Abstract: Dedicated to Professor Gleb Abakumov on the occasion of his 75th birthdaySince the discovery of ferrocene 60 years ago, [1] metallocenes have represented one of the most intriguing classes of organometallics. Numerous theoretical and experimental investigations of electronic structures of these prototypical systems form a basis for understanding the nature and fundamental properties of the metal-ligand delocalized chemical bonds. In contrast, intense chemical interest has been focused on these compounds during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We found that in vacuum, in the JT distorted ground state, the vertical −IP of cobaltocene was −5.33 eV within the PBE approximation and −5.45 eV when using the PBE0 functional. Both values are within 10% of the reported experimental values of −5.55 eV (from UPS studies) and −5.44 eV (from a zero kinetic-energy technique) . The cobaltocene family contains an even stronger reducing agent, decamethylcobaltocene, having a higher experimental vertical −IP of −4.71 eV .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We found that in vacuum, in the JT distorted ground state, the vertical −IP of cobaltocene was −5.33 eV within the PBE approximation and −5.45 eV when using the PBE0 functional. Both values are within 10% of the reported experimental values of −5.55 eV (from UPS studies) and −5.44 eV (from a zero kinetic-energy technique) . The cobaltocene family contains an even stronger reducing agent, decamethylcobaltocene, having a higher experimental vertical −IP of −4.71 eV .…”
Section: Resultssupporting
confidence: 80%
“…Both values are within 10% of the reported experimental values of À5.55 eV (from UPS studies) 67 and À5.44 eV (from a zero kineticenergy technique). 68 The cobaltocene family contains an even stronger reducing agent, decamethylcobaltocene, having a higher experimental vertical ÀIP of À4.71 eV. 67 Our calculated ÀIP is À4.25 eV, again within 10% error.…”
Section: Articlementioning
confidence: 93%
“…Two years later, Ketkov and Selzle () published a study which described the analysis of metallocenes with the help of MATI spectroscopy, in this case cobaltocene, Cp 2 Co. It was the first time that MATI spectra of such structures could be obtained.…”
Section: Mass Analyzed Threshold Ionizationmentioning
confidence: 99%
“…The metal–carbon distances obtained from the experimental data (electron and X-ray diffraction) and density functional theory (DFT) calculations were reported to increase in the line with Fe-Co-Ni. The Fe-C distances were found to be in the range from 2.007 to 2.064 Å [ 44 , 45 , 46 , 47 , 48 , 49 ], the Co-C distances from 2.070 to 2.120 Å [ 37 , 49 , 50 , 51 , 52 , 53 ] and the Ni-C distances from 2.148 to 2.196 Å [ 36 , 49 , 54 , 55 ]. This is explained by changing the electronic structure of the molecules in the line with FeCp 2 —CoCp 2 —NiCp 2 .…”
Section: Resultsmentioning
confidence: 99%